UPAYA KEPALA SEKOLAH DALAM MEWUJUDKAN SEKOLAH EFEKTIF DI ABAD KE-21 - Gaol, Nasib Tua Lumban; Nababan, Marina Letara (STKIP Pesisir Selatan, 2022)
The effective school is not a new topic in the education context globally. However, in the context of Indonesian education, this seems neglected. To create an effective school is the responsibility of the principal; therefore, it is very important to uderstand how the school principal can create an effective school. This study aims to investigate what efforts need to be conducted by the school principal in order to create an effective school. Based on the result of study, there are ten important efforts that need performed by school principal to create effective school, namely: (1)creating vision, mission and goals, (2)making school policies, (3)implementing leadership, (4)conducting crisis management, (5)developing, monitoring, and evaluating curriculum and learning, (6)increasing the professionalism of educators and administrators, (7)managing finances, (8)creating a conducive culture, (9)involving education stakeholders, and (10)optimizing the utilization of technology and information.